Kesadaran Mahasiswa terhadap Penyebaran Hoaks di Media Sosial sebagai Tantangan Kewarganegaraan Digital - Ardian Pradipta; Fitria Khoirunnisa Silitonga; Nurliza Syahfitri Lubis; Junita Friska (Universitas Negeri Medan, 2026)
The spread of hoaxes on social media has become one of the major challenges in achieving digital citizenship in Indonesia. This study aims to determine the level of student awareness regarding the dissemination of hoaxes on social media. A descriptive quantitative method with a survey approach was employed, involving 15 students as respondents. Data were collected through an online questionnaire and analyzed descriptively using frequency and percentage distributions. The results indicate that most students have a good level of awareness regarding hoaxes. They are able to identify false information, verify information before sharing it, and understand the negative impacts of hoaxes on society. In addition, students are aware of their role as responsible digital citizens in preventing the spread of false information. These findings suggest that digital literacy plays an important role in fostering critical and responsible attitudes in the use of social media. Therefore, strengthening digital literacy should continue to be promoted to support the creation of a healthy and responsible digital environment.